Nature of anti-circumvention standards of "bancarization", "derivative financial instruments" and "tax havens" - Zavaleta Álvarez, Michael (2018)
The present research seeks to demonstrate how tax norms of presumptive iure et de iure appearance or appearance of imperative fiction, in reality it is of juridical essence and tributary presumptive relative or iuris tantum.